2022
DOI: 10.1038/s41598-021-04416-z
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA, MTNR1B, and FKBP5 genotypes are associated with decreased odds of incident delirium in elderly post-surgical patients

Abstract: Despite the association between cognitive impairment and delirium, little is known about whether genetic differences that confer cognitive resilience also confer resistance to delirium. To investigate whether older adults without postoperative delirium, compared with those with postoperative delirium, are more likely to have specific single nucleotide polymorphisms (SNPs) in the FKBP5, KIBRA, KLOTHO, MTNR1B, and SIRT1 genes known to be associated with cognition or delirium. This prospective nested matched expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…One metaanalysis did not find an association between Melatonin Receptor-1B (MTNR1B) and delirium, 36 although studies published since then have provided more data in support of an association. 39 Melatonin signaling is particularly interesting given the strong link between circadian disruption and delirium. 11,12 The Influence of Environment on Delirium Clinical interventions that address common delirium precipitants have a dramatic influence on the incidence of delirium in hospitalized patients.…”
Section: Genetic Predisposition To Deliriummentioning
confidence: 99%
See 1 more Smart Citation
“…One metaanalysis did not find an association between Melatonin Receptor-1B (MTNR1B) and delirium, 36 although studies published since then have provided more data in support of an association. 39 Melatonin signaling is particularly interesting given the strong link between circadian disruption and delirium. 11,12 The Influence of Environment on Delirium Clinical interventions that address common delirium precipitants have a dramatic influence on the incidence of delirium in hospitalized patients.…”
Section: Genetic Predisposition To Deliriummentioning
confidence: 99%
“…One meta-analysis did not find an association between Melatonin Receptor-1B (MTNR1B) and delirium, 36 although studies published since then have provided more data in support of an association. 39 Melatonin signaling is particularly interesting given the strong link between circadian disruption and delirium. 11,12…”
Section: Genetic Predisposition To Deliriummentioning
confidence: 99%
“…Mechanistically, the motif stringency of XBP1s promoter binding sites dictates XBP1s's ability to drive 12-h rhythms of nascent mRNA transcription at dawn and dusk. Terrelonge et al 64 KIBRA, MTNR1B, and FKBP5 play an important roles in the complex relationship between delirium, cognition, and sleep, and warrant further study in larger, more diverse populations. Secretion of the stress hormone cortisol follows a circadian rhythm and is stimulated following stress exposure.…”
Section: Construction Of Rhythmic Gene Regulatory Network In Rat Pine...mentioning
confidence: 99%
“…FKBP5 single nucleotide polymorphisms (SNPs) ( i.e., rs3800373 and rs1360780 ) may increase suicide risk in individuals with a history of childhood trauma ( Roy et al, 2010 ; Womersley et al, 2022 ). As many studies have reported, FKBP5 variants have been linked to neuropsychiatric conditions, including depression, anxiety, posttraumatic stress disorder and cognitive impairment, all of which share some symptoms with sleep disturbance ( Wang, Shelton & Dwivedi, 2018 ; Hernández-Díaz et al, 2019 ; Terrelonge et al, 2022 ). In addition, a study reported a potential association between the FKBP5 rs9470080 variant and subjective health complaints, in which the FKBP5 rs9470080 CC genotype was associated with poor sleep quality complaints in the female working population ( Sannes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%